OPTIMISATION OF MARKETING AND LOGISTICS SYSTEMS AS A MEANS OF ENHANCING ECONOMIC VALUE AND SUSTAINABILITY IN THE PALM OIL INDUSTRY - Jeffry H. Sinaulan; Eka budi Yulianti; Sri Sugiarti (Adisam Publisher, 2026)
The palm oil industry is a strategic pillar of the Indonesian economy, making a significant contribution to Gross Domestic Product (GDP), exports and employment. However, the industry faces structural challenges in the form of a sub-optimal marketing system, a reliance on raw material exports, a negative image regarding sustainability, and logistical inefficiencies that increase distribution costs and reduce product quality. This study aims to examine strategies for optimising the marketing and logistics systems as an effort to enhance the economic value and sustainability of Indonesia’s palm oil industry. The method employed is a literature review using a descriptive qualitative approach. The research findings indicate that optimising the marketing system through the diversification of high-value derivative products (oleochemicals, biodiesel, oleofoods), strengthening sustainability certification (ISPO and RSPO), digitalising marketing (e-commerce and blockchain), and enhancing national branding can increase export value by up to 25–30 per cent and open access to premium markets. Meanwhile, optimising the logistics system through infrastructure modernisation (plantation roads, specialised ports), the integration of digital technology (Warehouse Management System, IoT, GPS tracking), the implementation of green logistics, and collaboration with state-owned logistics enterprises has the potential to reduce distribution costs by 25–30 per cent, maintain product quality, and lower the carbon footprint of the supply chain. Synergy between these two pillars creates a multiplier effect for enhancing global competitiveness, stabilising farmers’ prices, and ensuring environmental sustainability. This study recommends an integrated approach involving political commitment from the government through coherent cross-ministerial policies, sustainable investment from industry players, and inclusive multi-stakeholder collaboration to build an economical, sustainable, and inclusive palm oil industry for the welfare of the Indonesian people.